Amplifying Women’s Voices in Environmental Justice Movements through Gendered Communication for Stability and Development - Ekezue, Anthonia Ezenwa Ekezue (African Journal of Stability and Development (AJSD), 2025)
Environmental justice movements have increasingly highlighted the unequal distribution of ecological harms and benefits; however, women’s voices remain significantly underrepresented, especially in the Global South. This study investigated how gendered communication amplifies women’s participation in environmental justice movements and contributes to sustainable development. Guided by Feminist Political Ecology and Participatory Communication Theory, the research employed a qualitative design using secondary data from scholarly literature, NGO reports, and documented case studies. Thematic content analysis revealed that cultural, economic, and institutional barriers persistently hinder women’s involvement in environmental governance. Nonetheless, women strategically utilised community radio, oral storytelling, protest songs, and social media to advocate for environmental rights and mobilise communities. Case studies, such as Kenya’s Green Belt Movement and women-led resistance in Nigeria’s Niger Delta, emphasised the effectiveness of gendered communication in transforming environmental discourse and fostering resilience. Based on these findings, the study recommended mandating gender-inclusive environmental policies, supporting women-led advocacy platforms, and providing communication tools and training for grassroots women. It further called for participatory media strategies and more empirical research on digital feminism and environmental activism in underrepresented regions. The study concludes that inclusive, gendered communication is pivotal for equitable environmental outcomes, community stability, and long-term development.